2014
DOI: 10.1002/int.21652
|View full text |Cite
|
Sign up to set email alerts
|

A Fuzzy Dynamic Belief Logic System

Abstract: In this paper, we develop a fuzzy dynamic belief revision logic system. In our system, propositions take truth values in a set of multiple fuzzy linguistic terms, which people use in everyday life. And we use a uninorm operator to aggregate the linguistic truth values of the same proposition but drawn from two different rules because uninorms can reflect well that the aggregated result of two somehow negative truth values of the same proposition should be more negative, the aggregated result of two somehow pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…The values of two parameters must be subjectively chosen in the proposed methodology, namely the values of ξ and ζ, which represent the fixed allowances that are added to or subtracted from the cycle time estimate. Experts may choose various values for these parameters; therefore, various estimates must be aggregated . In addition, even when the experts use FBPNs with the same settings, the estimation results differ among runs because the initial values of the parameters are randomized.…”
Section: Methodsmentioning
confidence: 99%
“…The values of two parameters must be subjectively chosen in the proposed methodology, namely the values of ξ and ζ, which represent the fixed allowances that are added to or subtracted from the cycle time estimate. Experts may choose various values for these parameters; therefore, various estimates must be aggregated . In addition, even when the experts use FBPNs with the same settings, the estimation results differ among runs because the initial values of the parameters are randomized.…”
Section: Methodsmentioning
confidence: 99%
“…Some forms of fuzzy set have also been developed such as interval valued fuzzy sets (Zadeh 1973), vague sets (Gau and Buehrer 1993), rough fuzzy sets (Yang and Hinde 2010), and intuitionistic fuzzy sets and interval-valued intuitionistic fuzzy sets (Atanassov 1986(Atanassov , 1994. New theoretical and application fields of fuzzy set theory, such as the theory of fuzzy operators (Yager and Kacprzyk 1997;Xu 2005;Tan and Chen 2011;Meng and Tang 2013;Jing et al 2014;Zhou 2014) have also emerged. Manu applications (Bellman and Zadeh 1970;Zadeh 1996;Liao 2001;Adali et al 2009;Chen and Wang 2009;Jeguirim et al 2011;Chen 2012Chen , 2013 have shown the interest of fuzzy set based modeling.…”
Section: Cloud-based Design For Configurations Modelmentioning
confidence: 97%
“…In the above definition, formula is actually a specific uninorm, which is introduced by Yager and Rybalov and generalized further by Luo et al . Uninom operators have been applied into many domains such as automated negotiation, evidence aggregation in law, and fuzzy reasoning …”
Section: A Fuzzily Constrained Model For Gamesmentioning
confidence: 99%